Agriculture, CSME and common policy : issues and options - Francis, Diana E. (IICA Port of SpainTT, 2008)
Looks at the development of agriculture in the context of the CSME. Emphasizes the importance of integrating agriculture and briefly traces the history of regional cooperation in agriculture in response to external and internal influences.